A lattice Boltzmann fictitious domain method for modeling red blood cell deformation and multiple‐cell hydrodynamic interactions in flow. (14th January 2013) - Shi, Xing; Lin, Guang; Zou, Jianfeng; Fedosov, Dmitry A.
SUMMARY To model red blood cell (RBC) deformation and multiple‐cell interactions in flow, the recently developed technique derived from the lattice Boltzmann method and the distributed Lagrange multiplier/fictitious domain method is extended to employ the mesoscopic network model for simulations of RBCs in flow. The flow is simulated by the lattice Boltzmann method with an external force, while the network model is used for modeling RBC deformation. The fluid–RBC interactions are enforced by the Lagrange multiplier. To validate parameters of the RBC network model, stretching tests on both coarse and fine meshes are performed and compared with the corresponding experimental data. Furthermore, RBC deformation in pipe and shear flows is simulated, revealing the capacity of the current method for modeling RBC deformation in various flows. Moreover, hydrodynamic interactions between two RBCs are studied in pipe flow. Numerical results illustrate that the leading cell always has a larger flow velocity and deformation, while the following cells move slower and deform less.Copyright © 2013 John Wiley & Sons, Ltd.